2011
DOI: 10.1007/s10681-011-0436-8
|View full text |Cite
|
Sign up to set email alerts
|

Introgression of whitefly (Aleurotrachelus socialis) resistance gene from F1 inter-specific hybrids into commercial cassava

Abstract: The most widespread disease of economic importance of cassava is caused by whitefly vector, both as a single strain or combination of strains. A B 1 P 2 family was generated from the crosses of an inter-specific F 1 hybrid (CW 198-11) as a female parent with a commercial cassava cultivar (MTAI-8) as male parent at CIAT headquarters and evaluated in a high-pressure zone for whiteflies in Colombia. 227 genotypes were scored using a scale ranging from 1 (no leaf damage) to 6 (considerable leaf necrosis and defoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In Table 1, genotype NR11/0124 scored lowest in the mean CAD recorded while genotypes NR11/0123, NR11/128 and TMS 30570 recorded the highest (3). However, severities of CGM across the genotypes were relatively low [18,19]. It is a fundamental knowledge in crop science that crop growth has positive and significant relationship with yield [20,21] however; trend in disease severity and tuber yield differed.…”
Section: Resultsmentioning
confidence: 99%
“…In Table 1, genotype NR11/0124 scored lowest in the mean CAD recorded while genotypes NR11/0123, NR11/128 and TMS 30570 recorded the highest (3). However, severities of CGM across the genotypes were relatively low [18,19]. It is a fundamental knowledge in crop science that crop growth has positive and significant relationship with yield [20,21] however; trend in disease severity and tuber yield differed.…”
Section: Resultsmentioning
confidence: 99%
“…Cassava is a major source of carbohydrates for millions of people in several regions, particularly in developing countries. The cassava crop plays a vital role in reducing poverty and rural exodus because the use of technology required is minimal [2]. In addition to the social impact, cassava has attracted the interest of the agriculture business due to its multiple industrial uses of starch [3].…”
Section: Introductionmentioning
confidence: 99%
“…Alves et al (2011) assessed 14 accessions of six wild Manihot species with regard to biological aspects of M. tanajoa and found that the life cycle (larva-adult period) ranged from 5.76 to 8.18 days. The accessions of wild M. anomala species formed the group showing the longest mite development period, whereas M. peruviana and M. flabellifolia accessions showed shorter larva-adult periods.…”
Section: Resultsmentioning
confidence: 99%
“…are adapted to semiarid conditions and are potential sources of genes for drought tolerance; 4) the roots of interspecific hybrids of M. esculenta ssp. flabellifolia contain a high protein content (AKINBO et al, 2012a); 5) M. flabellifolia accessions and interspecific crosses of M. esculenta ssp. flabellifolia exhibit different levels of resistance to the whitefly Aleurotrachelus socialis Bondar (CARABALI et al 2010); and 6) resistance to A. socialis can be introgressed in interspecific hybrids of commercial cassava (AKINBO et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%